Mediation Role of Job Satisfaction on Employee Performance A Study on Distribution Company - Dini, Yuli Indah Fajar; Rina; Mon, Muhammad Donal (Jurnal Manajemen, 2024)
This study explores how career development, competence, and compensation influence employee performance, with job satisfaction serving as a mediating factor. According to data from the Central Bureau of Statistics (BPS), there are 2,153 distributor companies in Batam City, employing 259,749 workers. The study sampled employees from these companies, collecting data from 387 respondents via online questionnaires distributed through Google Forms. Out of these, 313 responses were valid and analyzed, while 74 were discarded due to invalidity. The majority of respondents were female (54.63%), with males making up 45.37%. The research employs a descriptive quantitative approach, using quantitative data analysis techniques. The sampling method involved surveys with 29 questions, and data were processed using the Partial Least Square (PLS) application. The study tested 10 hypotheses: seven examining direct relationships (H1-H7) and three examining indirect relationships (H8-H10). The findings reveal that nine out of the ten hypotheses were supported with significant positive results, while one hypothesis specifically H1, which proposed that career development impacts employee performance was not supported.